UMPSA Foundation, PUNB, and Maxis Berhad extend help with cooking essentials for off-campus students - Nor Azhar, Ahmad (UMPSA, 2024)
PEKAN, 22 March 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Foundation, Perbadanan Usahawan Nasional Berhad (PUNB), and Maxis Berhad have stepped forward to assist UMPSA students living off-campus with cooking essentials through the Salam Cinta Ramadan Programme.